Analisis Pembiayaan Kesehatan Di Daerah Istimewa Yogyakarta - Arie Risdiyanti; Paulina Samuellia; Umi Kusuma (Pascasarjana Universitas Jember, 2022)
Health for all is the goal of sustainable health development as a form of joint investment, commitment to improve the quality of life and the health status of the community as high as possible, according to the mandate of UU RI Number 36 of 2009. Portraits of the complexity of national health problems are also found in DIY, one of the provinces that has been privileged with the enactment of Law No. 13 of 2012 concerning the privileges of the Special Region of Yogyakarta (DIY). The purpose of this study is to photograph health financing in DIY and its utilization. This study uses a descriptive research method with literature review from various references (Library Research) to analyze DIY health financing policies in 2021. The results of the study show that the life expectancy of DIY reached 74.92% in 2019 and became the best nationally, but on the other hand the poverty rate is also very high compared to the national figure so that the potential for vulnerability to disease and financial resilience is low when there is no health insurance from the government. , the portion of the health budget in DIY of 6.6% is still less than the mandate of the Health Law of 10% of the total APBD, and the specialty of DIY has Danais that distinguishes it from other provinces in Indonesia, although the portion of Danais is smaller but its allocation can be maximized to support efforts to increase public health status.